Congenital cytomegalovirus infection after maternal primary infection in a patient with systemic lupus erythematosus: A case report and literature review. (February 2022) - Nakamura, Eri; Isoda, Kentaro; Kotani, Takuya; Hiramatsu, Yuri; Wada, Yumiko; Fujiki, Youhei; Fujita, Daisuke; Takeuchi, Tohru
Background: Management of infectious complications in pregnant women receiving immunosuppressive therapy for systemic lupus erythematosus (SLE) is important. Maternal infection with cytomegalovirus (CMV) often causes congenital CMV infection in the foetus. Thus far, there are only few reports on congenital CMV infection after maternal reactivation in patients with SLE. We report the first case of congenital CMV infection after maternal primary infection in a patient with SLE. Case presentation: A 19-year-old Japanese primigravida with SLE received treatment with prednisolone 3 mg/day and azathioprine 75 mg/day at conception. At 7 weeks of gestation, she suddenly developed fever and had decreased white blood cell and platelet counts and elevated aspartate aminotransferase and alanine aminotransferase levels. These clinical findings led to a diagnosis of SLE exacerbation. The prednisolone dose was increased to 15 mg/day, and hydroxychloroquine (200 mg/day) was administered. Consequently, all clinical findings normalised at 12 weeks. At 19 weeks, foetal ultrasound findings revealed oligohydramnios, brain hypoplasia, ventriculomegaly and hyperechogenic bowel. Maternal serological test results indicated increased CMV-specific IgG and IgM levels, low IgG avidity (26%), and positive CMV antigenemia. The foetus was diagnosed with symptomatic congenital CMV infection transmitted from the maternal primary infection. After counselling about the severe prognosis of the foetus, the mother decided to terminate her pregnancy and underwent artificial abortion at 21 weeks. Discussion: The foetus of a mother with SLE who is receiving immunosuppressive therapy may be at increased risk of transmission and aggravation of congenital CMV infection; thus, preventive management and screening for congenital CMV infection during pregnancy are recommended for such patients. Maternal CMV infection shows clinical findings similar to those of SLE exacerbation, and careful differential diagnosis by maternal serological evaluation and foetal ultrasound scans is required.